Description of Dustman’s Behavior Using Personal Protective Equipment at The Environment and Cleaning Department of Kupang City - Siti Zaenab Ahmad; Johny A. R. Salmun; Agus Setyobudi (Lontar : Journal of Community Health, 2022)
The importance of using PPE for waste transport officers is to prevent potential hazards in the workplace. This study identified predisposing factors (knowledge, attitudes, comfort), enabling (availability of PPE and socialization), and reinforcing (supervision and policy) of the behavior of using PPE for waste transporters in 2020. This study is descriptive. The population of this study was 181 waste transport officers at the Environmental Service and Cleanliness of Kupang City. The sampling technique is simple random sampling and a sample of 64 officers. Data were analyzed using a frequency distribution table. The results showed that most respondents had good knowledge and a positive attitude towards PPE with 95.3% and 92.2%. However, as many as 89,1% of respondents expressed uncomfortable feelings using PPE. PP was not available (100%), socialization about PPE during 2020 was never carried out (100%), supervision of the use of PPE during 2020 did not exist (100%), and leadership policies related to PPE during 2020 did not exist (100%). In addition, all respondents did not use PPE completely (100%). The Kupang City Environment and Hygiene Service should consider the condition of PPE that is damaged and unsuitable for use and supports the proposal of parties in the budget so that the office has PPE for waste transport officers.